Fertility and Pregnancy Outcome after Myoma Enucleation by Minilaparotomy under Microsurgical Conditions in Pronounced Uterus Myomatosus - Floss, K.; Garcia-Rocha, G.-J.; Kundu, S.; von Kaisenberg, C. S.; Hillemanns, P.; Schippert, C. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Besides the typical complaints and symptoms, myomas can cause sterility, infertility and complications during pregnancy. Laparoscopic interventions reach their limits with regard to organ preservation and the simultaneous desire to have children in the removal of multiple and larger intramural myoma nodes. The aim of this study is to examine fertility status and pregnancy outcome after myoma removal by minilaparotomy (skin incision maximal 8 cm) in women with pronounced uterus myomatosus. Materials and Methods: This retrospective study makes use of the data from 160 patients with an average age of 34.6 years. Factors analysed include number, size and localisation of the myomas, complaints due to the myoma, pre- and postoperative gravidity, mode of delivery, and complications of birth. Results: Indications for organ-sparing myoma enucleation were the desire to have children (72.5 %), bleeding disorders (60 %) and pressure discomfort (36.5 %). On average 4.95 (SD ± 0.41), maximally 46 myomas were removed. The largest myoma had a diameter of 6.64 cm (SD ± 2.74). 82.5 % of the patients had transmural myomas, in 17.5 % the uterine cavity was inadvertently opened. On average the operating time was 163 minutes (SD ± 45.47), the blood loss 1.59 g/dL (SD ± 0.955). 60.3 % of the patients with the desire to have children became pregnant postoperatively. 75.3 % of the pregnancies were on average carried through to the 38th week (28.4 % vaginal deliveries, 71.6 % Caesarean sections). In the postoperative period there was one case of uterine rupture in the vicinity of a previous scar. Discussion: By means of the microsurgical “mini-laparotomy” even extensive myomatous uterine changes can, in the majority of cases, be operated in an organ-sparing manner with retention of the ability to conceive and to carry a pregnancy through to maturity of the infant. The risk for a postoperative uterine rupture in a subsequent pregnancy and during delivery is minimal.
Keywords: myoma; sterility; myoma enucleation; pregnancy outcome; minilaparotomy; microsurgery